2013
DOI: 10.1111/jvim.12146
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Coagulation Activation, Endothelial Stimulation, and Inflammation in Dogs with Babesiosis

Abstract: Background: Babesia infections in dogs can result in a wide range of clinical and laboratory presentations, including coagulopathy. Expression of intercellular adhesion molecule-1 (ICAM-1) and von Willebrand factor (vWF) in dogs with babesiosis is unknown.Objectives: Whether inflammation in babesiosis triggers activation of ICAM-1 and the coagulation system. Animals: Twelve and 10 dogs with naturally occurring babesiosis before and after antiparasitic treatment, respectively, were compared with 10 healthy dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 63 publications
2
46
1
1
Order By: Relevance
“…Results of the study of Matijatko et al [89] indicated that B. canis induces a marked APR, with C-reactive protein (CRP) and serum amyloid A (SAA) being the markers which showed the highest response and may be useful in monitoring the response to treatment. Excessive proinfl ammatory activity with increased concentrations of CRP was also detected in natural infection with B. canis [91] and experimental one with B. gibsoni [108]. In our proteomic study of serum changes in canine babesiosis, a number of differentially expressed proteins involved in infl ammation mediating the acute phase response, including CRP, were identifi ed in dogs with babesiosis [84].…”
Section: Systemic Infl Ammatory Response Syndromementioning
confidence: 92%
See 3 more Smart Citations
“…Results of the study of Matijatko et al [89] indicated that B. canis induces a marked APR, with C-reactive protein (CRP) and serum amyloid A (SAA) being the markers which showed the highest response and may be useful in monitoring the response to treatment. Excessive proinfl ammatory activity with increased concentrations of CRP was also detected in natural infection with B. canis [91] and experimental one with B. gibsoni [108]. In our proteomic study of serum changes in canine babesiosis, a number of differentially expressed proteins involved in infl ammation mediating the acute phase response, including CRP, were identifi ed in dogs with babesiosis [84].…”
Section: Systemic Infl Ammatory Response Syndromementioning
confidence: 92%
“…Although almost all infected dogs are presented with severe thrombocytopenia, none develop haemorrhage. Thrombocytopenia may result from immune-mediated platelet destruction, platelet sequestration in the spleen, elevated body temperatures or disseminated intravascular coagulation (DIC) [91]. The severity and rapid recovery of the platelet counts have led to the suggestion that immune-mediated mechanisms are involved.…”
Section: Leucopenia and Thrombocytopeniamentioning
confidence: 99%
See 2 more Smart Citations
“…Following treatment with imidocarbdipropionate CRP values decreased [38]. Furthermore, CRP was not associated with the outcome in Babesia rossi infection in dogs but none of the survivors had on the day of admission CRP levels lower than than 63.2 mg/L [39].…”
Section: Dogsmentioning
confidence: 85%